Penerapan Metode Double Exponential Smoothing untuk Menganalisis Peramalan Produksi Ekspor dan Konsumsi Minyak Sawit Indonesia - Muhammad Akshay Kumar; Eman Lesmana; Julita Nahar (LPPM UNIBI, 2020)
Agricultural sector is one of the flagship sector that has great potential in Indonesia. One of Indonesia's flagship agricultural commodities is palm oil. But the last few years do not meet the demand for oil palm and this causes the supply for domestic consumption in Indonesia is not fulfilled. In addition the high export demand does not match the amount of production available. To offset and develop Indonesia's palm oil required a policy and planning. The study discusses the implementation of the Double Exponential Smoothing method to analyse forecasting the amount of production, exports, and domestic consumption of Indonesian palm oil. Based on the results of the forecast shows in the year 2020 the projected production of palm oil in Indonesia is not able to fulfill the demand for export and domestic consumption demand in Indonesia with a difference of 2,191,797.14 tons. To overcome these differences can increase production through land expansion and increased productivity by adding the use of potassium fertilizers and land rejuvenation (replanting).